2005
DOI: 10.17660/actahortic.2005.680.8
|View full text |Cite
|
Sign up to set email alerts
|

Essential Leaf Oils From Melaleuca Cajuputi

Abstract: Hydrodistillation of cajuput (Melaleuca cajuputi) leaves collected from 6 sites in Narathiwat gave different yields of cajuput oils. The maximum oil yield (0.97%) was obtained from leaves from Ban Koke Kuwae, Thambon Kosit, and Amphur Tak Bai. The oil yields from leaf samples of other sites were 0.84% from Ban Pha Ye and Thambon Sungai Padi in Amphur Sungai Padi; 0.76% from Ban Lubosama, and Thambon Pasemat, in Amphur Sungai Kolok; 0.70% from Ban Tha Se, and Thambon Kosit, in Amphur Tak Bai; 0.66% from Ban Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 2 publications
1
9
0
1
Order By: Relevance
“…Although most of the previous study found high yield of 1,8-cineole [12], this research found differentcompound name caryophyllene in the highest percentage. It is similar with study that no 1,8-cineole or contained very lowquantity (< 3%) of this compound in those areas [13]. Nevertheless, it was reported that active compound 1,8-cineole can cause skin irritation even in low quantities.…”
Section: Chemical Profilingsupporting
confidence: 88%
See 1 more Smart Citation
“…Although most of the previous study found high yield of 1,8-cineole [12], this research found differentcompound name caryophyllene in the highest percentage. It is similar with study that no 1,8-cineole or contained very lowquantity (< 3%) of this compound in those areas [13]. Nevertheless, it was reported that active compound 1,8-cineole can cause skin irritation even in low quantities.…”
Section: Chemical Profilingsupporting
confidence: 88%
“…The differences of essential oils in chemical constituents depend on many factors such as climaticchanges and soils type. Geographic variation also affected the chemical composition of oils from leaves [13]. Reference [18] claimed that thefactor influencing the qualityessential oils include variety of plant species, cultivatingprocess, maturation plants, plant storage and methods of extraction.…”
Section: Chemical Profilingmentioning
confidence: 99%
“…Besides plant extracts, essential oils have also shown very strong repellent and toxic activity against Formosan subterranean termite due to presence of volatile compounds [43]. Moreover, plant origin monoterpenes were proved highly toxic to Coptotermes formosanus [44].…”
Section: Discussionmentioning
confidence: 99%
“…Gelam provides a renewable resource of woods and poles and potentially can be used to produce cajuput oil, a secondary compound from its leaves which may be useful for pharmaceutical industry. The 'cajuput' oil industry is surviving well in Indonesia [32] and Thailand [33]. However, similar industry is still untapped in Malaysia or Terengganu, possibly due to low essential oil content in its leaves, about <1% of it dry weight [34].…”
Section: Changes In Coastal Landscapes and Implications For Ecosystemmentioning
confidence: 99%